Eclipse - Meyer, Stephenie, 1973- (New York : Little, Brown and Co.; Atom, 2008)
Bella must choose between her friendship with Jacob, a werewolf, and her relationship with Edward, a vampire, but when Seattle is ravaged by a mysterious string of killings, the three of them need to decide whether their personal lives are more important than the well-being of an entire city.
"Megan Tingley books."
Includes poster on reverse side of book jacket and t-shirt transfers in pocket attached to p. 3 of cover.
Keywords: Vampires -- Fiction; Werewolves -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Seattle (Wash.) -- Fiction; Washington (State) -- Fiction